Pengenalan Arsitektur melalui Proses Pembelajaran Anak di Sekolah Pemulung - Andi Karina Deapati; Mohammad Mochsen Sir; Ria Wikantari; Abdul Mufti Radja; Syahriana Syam; Afifah Harisah (Faculty of Engineering UNHAS, 2021)
When children learn about architecture, they can build things with their own hands, feel the satisfaction of being a problem solver and creating something great. Collaborating with school teachers, we can encourage visual literacy and explain math, science, social, visual arts and even English concepts to children through various methods to evaluate their learning performance. This introduction to architecture for children took place at the Sekolah Impian, which is a school for children whose parents, on average, work as garbage scavengers in Makassar. The method used is to be directly involved in the learning process, using a combination of contextual and cooperative learning models. Through the introduction of architecture in this lesson, almost all children seemed very enthusiastic in learning because it was filled with activities they enjoyed, such as drawing, coloring, telling stories, and making models. The results of this activity are expected to make architecture a fun and useful active learning medium for school teachers, and to provide a pleasant picture of the architects’ life and/or architecture students so that children are motivated to achieve a better education and life in their future.